If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 + (1 + -4x) = 1 + x + -2(x + -16) Remove parenthesis around (1 + -4x) 3x + 4 + 1 + -4x = 1 + x + -2(x + -16) Reorder the terms: 4 + 1 + 3x + -4x = 1 + x + -2(x + -16) Combine like terms: 4 + 1 = 5 5 + 3x + -4x = 1 + x + -2(x + -16) Combine like terms: 3x + -4x = -1x 5 + -1x = 1 + x + -2(x + -16) Reorder the terms: 5 + -1x = 1 + x + -2(-16 + x) 5 + -1x = 1 + x + (-16 * -2 + x * -2) 5 + -1x = 1 + x + (32 + -2x) Reorder the terms: 5 + -1x = 1 + 32 + x + -2x Combine like terms: 1 + 32 = 33 5 + -1x = 33 + x + -2x Combine like terms: x + -2x = -1x 5 + -1x = 33 + -1x Add 'x' to each side of the equation. 5 + -1x + x = 33 + -1x + x Combine like terms: -1x + x = 0 5 + 0 = 33 + -1x + x 5 = 33 + -1x + x Combine like terms: -1x + x = 0 5 = 33 + 0 5 = 33 Solving 5 = 33 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x-37.5=-3.41 | | -8v+6(v-5)=-28 | | 5ln(3x)+6=31 | | (3x+1)(4x+1)(6x+1)(12x+1)=2 | | -9.5x+39.9=7.5 | | 10-6y+4y=9 | | -0.9+3.6x=0.18 | | 7x+2x+36=180 | | 90=8f | | 4tan(t)+9=8 | | -11m=77 | | 4x-600=600 | | 5x*3+5=10 | | 0.04(150+0.25y)-0.08y=-36 | | 6(a+7)=7(a+9) | | 9x-21+9=2(50-x) | | y=-3*-3+3 | | -29=7q+27 | | 5(x+4)-2=33 | | -29= | | y=-3*-6+3 | | 12a=49 | | 5q-17=43 | | H=6+75t-16t^2 | | 6w^2+10w^2=c^2 | | (4x+4)= | | y^2-4x^2+8y=0 | | 4m-16=-32 | | 4(14x)=7x+40 | | -11c+10=45 | | 6sin(4x)=5 | | 1.5*sin(93.3-x)=2.7*sin(x) |